Desert Mould: Witold Odrzywolski and His Work on Crude Penicillin in a Military Hospital in the Middle East in 1944 - Łotysz, Sławomir (Kwartalnik Historyczny, 2020)
The author analyses the activities of Witold Odrzywolski, who in 1944 was the first Pole to produce penicillin, in a military hospital in the Middle East. The paper contextualizes this achievement in a broad array of the scientific, medical, military and political determinants of the era.